Experiences of Navigator, a Finnish patient-segmentation service, in primary care: A mixed-methods study - Riikka Riihimies; Elise Kosunen; Tuomas Koskela (Finnish Journal of eHealth and eWelfare, 2021)
Aging and multimorbid populations burden health services worldwide. Segmenting patients with similar health service needs into different groups and guiding care providers to tailor services to these groups could reduce this burden. Methods of patient segmentation have been based on, e.g., databases. However, the Finnish patient-segmentation innovation Navigator (Suuntima) considers patients’ perspectives on their coping in everyday life, as well as professionals’ views of the patients’ state of health. The segmentation is based on questions. The resulting care pathway related to the group helps professionals to coordinate patients’ health care and patients to utilize appropriate services.